Nevalstiskie teātri Latvijā. Tradīcija un inovācijas - Grīnvalte, Vita (Latvijas Universitāte, 2013)
Nevalstiskie teātri ir neatņemama Latvijas teātra sastāvdaļa kopš 20.gadsimta 80.gadu beigām un 90.gadu sākuma, kad līdzās valsts repertuārteātriem sevi pieteica privātie teātra formējumi. Maģistra darbs „Nevalstiskie teātri Latvijā. Tradīcija un inovācijas” skaidro nevalstiskā teātra jēdzienu un pēta nevalstisko teātru kustības nozīmi atšķirīgos laikposmos, analizē to darbības principus un vērtē radošo darbību.

Non governmental theater is an integral part of Latvian Theater since late 80’s and early 90’s of the 20th century when private theater formations presented themselves alongside state repertoires. Master paper „Non Governmental Theaters in Latvia. Traditions and Innovations” explains the concept of non governmental theater and explores importance of non governmental theater’s movement in different periods, analizes its action principles and values its creative activities.
Non-State Subsidized Theatre Companies in Latvia. Tradition and Innovation
Keywords: Filoloģija